2008
DOI: 10.3892/or.19.3.609
|View full text |Cite
|
Sign up to set email alerts
|

Expression and cellular localization of TSC-22 in normal salivary glands and salivary gland tumors: Implications for tumor cell differentiation

Abstract: TGF-ß-stimulated clone-22 (TSC-22) was reported to be a differentiation-inducing factor which negatively regulates the growth of salivary gland cancer cells. In the present study, we examined the expression of TSC-22 in salivary gland tumors by immunohistochemistry. In pleomorphic adenoma (PA), most of the sparse myoepitheliallike tumor cells, which are considered as the differentiated cells because they produce extracellular matrix, expressed TSC-22. However, only a limited number of cases of the solid myoepi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Consistently, gene targeting of TSC-22 enhanced the proliferation of hematopoietic precursor cells (HPCs) (40). In addition, TSC-22 was also reported to promote cell differentiation and apoptosis (7,18). Moreover, the Drosophila homolog of TSC-22 was suggested to be in the same genetic pathway as Dpp (a bone morphogenetic protein [BMP] homolog) during fly eye development (33), and it was also shown to induce erythroid cell differentiation by facilitating TGF-␤ signaling (4).…”
mentioning
confidence: 68%
“…Consistently, gene targeting of TSC-22 enhanced the proliferation of hematopoietic precursor cells (HPCs) (40). In addition, TSC-22 was also reported to promote cell differentiation and apoptosis (7,18). Moreover, the Drosophila homolog of TSC-22 was suggested to be in the same genetic pathway as Dpp (a bone morphogenetic protein [BMP] homolog) during fly eye development (33), and it was also shown to induce erythroid cell differentiation by facilitating TGF-␤ signaling (4).…”
mentioning
confidence: 68%
“…Fat4 — originally described as a tumor suppressor in Drosophila — was later shown to be a candidate tumor suppressor gene in breast cancer cell lines and primary tumors (40). Tsc22d1 is also a known tumor suppressor by promoting cell growth, survival, and proliferation and by preventing apoptosis, and has been associated with several cancers types (e.g., breast cancer, salivary gland cancer, prostate cancer) (4143). It has been shown to be highly expressed in the lung (44).…”
Section: Discussionmentioning
confidence: 99%
“…Vice versa, downregulation of TSC-22 enhances cellular proliferation in human salivary gland cancer cell lines in vitro and in vivo Nakashiro et al, 1998]. Accordingly, a decrease in TSC-22 is observed in several tumours such as large granular lymphocyte leukaemia, glioblastomas, salivary gland and prostate carcinomas [Shostak et al, 2003;Rentsch et al, 2006;Doi et al, 2008;Yu et al, 2009] as well as during chemically induced liver carcinogenesis [Iida et al, 2005] and was identified as an acute molecular marker of non-genotoxic rodent hepatocarcinogenesis [Michel et al, 2005;Fielden et al, 2007]. In line with an inhibitory role of TSC-22 in cell proliferation, we detected a threefold induction of TSC-22 protein in confluent NIH3T3 cells.…”
Section: Discussionmentioning
confidence: 99%